THE IMPLEMENTATION OF EDUCATION CHARACTER MANAGEMENT AT STATE ISLAMIC SENIOR HIGH SCHOOL (MAN) 2 MODEL MEDAN - Deliani Deliani (State Islamic University of North Sumatra Indonesia, 2020)
The purpose of this study is to identify the values of character education that are applied in Madrasah Aliyah and to find out the efforts carried out in character education management. The method used in this study is in the form of qualitative field research, in which data collection techniques are carried out through interviews, observation and documentation. Furthermore, in analyzing data, the transferability, conformability, and triangulation data models are used. The results of this study indicate. The process of character building in Madrasah Aliyah starts from the transformation of values (both inside and outside the classroom), modeling, civilizing, motivating, and enforcing rules. Keywords: Implementation of Education Character Management, Islamic Senior High School,